Prevalence and sociodemographic risk factors of soil-transmitted helminth infections in pregnant women, Kisii County, Kenya - Ratemo, Geoffrey G.; Musyoki, Stanslaus K.; Nyanchongi, Benson O.; Otwabe, Julius S. (International Journal Of Community Medicine And Public Health, 2026)
Background: Soil-transmitted helminths (STH) are the most prevalent parasitic infections affecting humans worldwide. However, the levels of infection in pregnant women and the information on risk factors in Kisii County is not known. The aim of this study was to determine the prevalence of STH in pregnant women and the influence of sociodemographic factors. Methods: A cross-sectional study of 384 pregnant women, selected through random sampling. A questionnaire was used to collect sociodemographic data. Faecal samples were examined microscopically with saline and formal-ether concentration techniques to identify helminth species. Data analysis involved proportions, logistic regression and Chi-square, with p<0.05 deemed significant. Results: Results indicated that the prevalence of STH among pregnant women was 144 (37.5%) where A. lumbricoides was 94 (24.5%), Hookworm 21 (5.5%), S. stercolaris 5 (1.3%), T. trichiura 1 (0.3%) and E. vermicularis 1 (0.3%). Additionally, mixed infections were observed; A. lumbricoides and Hookworm 16 (4.2%), A. lumbricoides and T. trichiura 2 (0.5%), T. trichiura and E. vermicularis 1 (0.3%) and A. lumbricoides and E. vermicularis 1 (0.3%). Economic activity was significantly associated with STH infections (ꭕ2=63.485, p=0.01). Subsistence farming in particular was significantly associated with STH infections (ꭕ2=4.580, p=0.03The income levels had a significant association with STH infections (ꭕ2=16.833, p< 0.01). Lower levels of income were significantly associated with STH infections (ꭕ2=10.96, p<0.01). Conclusions: STH infections are common in pregnant women at KTRH, especially subsistence farmers. Routine diagnosis, health education and treatment during antenatal care are critical. These findings could guide healthcare workers in eliminating STH infections in pregnancy.